THE RISK FACTORS OF DEATH DUE TO CORONA VIRUS DISEASE 19 IN KENDARI CITY: CORONA VIRUS DISEASE 19 - Karmila Karmila; Timbul Supodo; Sunarsih Sunarsih (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background : Corona virus Disease 2019 or Covid-19 is an infectious disease caused by Severe Acute Respiratory Syndrome Corona virus 2 (SARS-Cov-2). Data from the Kendari City Health Office from January to December 2020, the number of confirmed cases of Covid-19 was 3,874 cases with 56 deaths spread throughout Kendari City. The high death rate from corona virus disease19 is caused by several factors. The research objective was to determine the risk factors for death due to corona virus disease 19 (covid-19) in Kendari City. Methods: This type of research is a case control study conducted from March to April 2021, the number of sample  are 49 cases taken by random sampling and 49 controls. Results: Based on the Odds Ratio (OR) value of pneumonia disease is 8,624> 1, OR of Diabetes Mellitus is 7,994> 1, and the respondent's OR of hypertension is 8,653> 1. Conclusion: Pneumonia, diabetes mellitus, and hypertension are the risk factors of  death from Covid-19 in Kendari City in 2020. A person suffering from hypertension has the greatest risk of death. Furthermore, the second greatest risk for death is in someone who has pneumonia.